Introducing digital storytelling to english teachers in Malaysia: what are their concerns? - Yit, Sim Lee; Siew, Ming Thang; Hazita Azman, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
This study shares the findings of a study that explores the initial concerns of three teachers who introduced digital storytelling as a project-based learning activity in their ESL (English as a Second Language) classrooms. Digital storytelling is one of the many new technologies in the Web which could be harnessed to enhance learning because it can encompass many topics in different educational contexts. A digital story has a narration overlay and sometimes a music background; combining images, audio, and video to tell a story or to make a factual presentation. The purpose of this paper is to report on three teachers’ initial concerns using the Stages of Concern (SoC) dimension which utilizes these three techniques: one-legged interview, open-ended concerns statement, and Stages of Concern Questionnaire (SoCQ). The analysis of the teachers’ concerns revealed that each teacher’s personal concerns can be related to one of the four classifications of teachers in relation to ICT integration in practice: contented traditionalist, selective adopter, inadvertent user, and creative adapter. The discussion of findings implies that the teachers’ personal concerns can be associated with the teacher ICT characteristics, as well as their job responsibilities and experiences in using ICT in the language classroom. The paper ends by highlighting the need to investigate teachers’ concerns from a bigger sample population before conclusive findings can be made.